1973
DOI: 10.1128/aem.25.2.169-172.1973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Variations in Conditions of Incubation upon Inhibition of Staphylococcus aureus by Pediococcus cerevisiae and Streptococcus lactis1

Abstract: The effects of pH, temperature, proportion of Staphylococcus aureus in the inoculum, various strains of effector organism, and various strains of S. aureus were examined for their influence on interactions between staphylococci and effector organisms in associative culture. In general, small changes in pH had little effect upon either growth of S. aureus or production of enterotoxin in associative culture. Inhibition of growth of S. aureus caused by effector organisms was much greater at 25 than at 30 C. Propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…It is important to note that S. lactis inhibits the growth of S. aureus in vitro [ 35 ]. An independent study also showed that an enhanced Th1 response was beneficial to attenuate infection [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that S. lactis inhibits the growth of S. aureus in vitro [ 35 ]. An independent study also showed that an enhanced Th1 response was beneficial to attenuate infection [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous examinations [52] have shown the best reduction ability for the concentrations of S. aureus isolates (7142; 10614) and PM, which were also used in the present trials. For the application of S. aureus and LAB, a ratio of 1:10 was used according to the findings of previous studies [53,54].…”
Section: Antimicrobial Activity Of a Phage Mixture And A Lactic Acid mentioning
confidence: 99%